Towards revision of the UN drug control conventions: Harnessing like-mindedness - David Bewley-Taylor (International Journal of Drug Policy, 2013)
Almost all nations are currently parties to the UN international drug control conventions of 1961, 1971 and 1988; treaties that taken together form what can be usefully called the global drug prohibition regime. Despite interpretative tensions around some national policy approaches that deviate from punitive prohibition, the inherent flexibility within the conventions permit members of the regime some policy space at the national level. Should they wish to do so, however, states already pushing at the limits of the regime would only be able to expand such national policy space via an alteration in their relationship to the UN drug control conventions and the prohibitive norm at the regime’s core. Mindful of the political and procedural dynamics of the regime, this article argues that the formation and operation of a group, or groups, of like-minded nations appear to be the most logical and promising approach for some form of substantive treaty revision. It also argues, however, that the varied nature of dissatisfaction with the prohibitive ethos of the regime combines with the character of drug policy to generate dilemmas for the like-minded group (LMG) approach. Nonetheless, the article suggests that within the current policy environment it is plausible to foresee the construction of groupings around a number of issue areas: traditional and religious drug use, cannabis regulation, technical issues relating to inconsistencies within the conventions and UN system-wide coherence. These potential groups provide the basis for discussion of a number of possible scenarios for treaty revision and highlight essential commonalities of approach that should be considered whatever the route towards reform.